Exploring College Student Vocabulary Acquisition Through Songs - Lerebulan, Dorthea; Titirloloby, Piter; Mailuhuw, Lendy (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2025)
The research objectives of this research are to explore the experiences of second semester students in learning English vocabulary using songs and to explore second-semester students' perceptions of the use of songs in vocabulary acquisition. The method used was qualitative descriptive. In this study, the researcher used interviews, open questionnaires, and documentation, and to analyze the research results, the researcher used thematic analysis method which was combined with thematic content analysis. The results showed that learning English vocabulary through songs provided a fun and meaningful learning experience for second-semester students in the English Education Study Program at Lelemuku Saumlaki University.